DETERMINATION OF MORPHINE USING MOLECULARLY IMPRINTED POLYMERS BASED ON DIFFERENT MONOMERS - Y. K. Al-Bayati, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to investigate for the particular adsorption of morphine, precipitation polymerization technology was used to create molecularly imprinted polymers. Using benzoyl peroxide as the initiator, ethylene glycol dimethacrylate as the crosslinker, and allyl chloride and styrene as the functional monomers. This MIP demonstrated a maximum morphine adsorption capacity of 38.24 mg/g at a bulk morphine concentration of (20,40,60,80,100) ppm in acetonitrile solution, one of the greatest talents recorded in the literature to date. Thermodynamic analysis, instrumental characterisation, adsorption studies, and suggested mechanisms all verified the molecularly imprinted polymers adsorption capacity, selectivity, reusability, and mechanical and chemical stabilities. FTIR, UV-vis, and scanning electron microscopy were used to monitor the analytes. The range of the relative standard deviations (RSD%) for three measurements made during two patient repeat tests at 20–100 ppm of morphine is (1.587–4.545) %. The range of (102-105) is the relative recoveries obtained for morphine in human urine samples that were spiked.